5PSQ-161 Securing storage of high-risk medicines in a care unit: where are we now?. (March 2019) - Stenuit, S; Tchuente Modjo, G; Pardo, A
Abstract : Background: In our country, a Platform for Continuous Improvement of Quality of Care and Patient Safety has set the following target for hospitals: by the end of 2018, 100% of high-risk medicines (HRMs) will be correctly identified and stored in a pilot unit according to the established procedure. Purpose: To evaluate, through a monthly audit, the compliance with the tidying procedure of HRMs established in the pilot unit. Material and methods: The internal medicine ward was the pilot unit chosen for this work. The tidying procedure of HRMs implemented in this unit includes: the withdrawal from the unit of all concentrated electrolytes; the storage of each HRM in a labelling area on which appears an HRM symbol in addition to the usual drug information; the HRM storage in a zone marked 'HRM', except insulins, narcotics and infusions which are respectively stored in the refridgerator, the narcotic chest and the infusion cabinet; and the remoteness of HRMs 'Look Alike – Sound Alike' from each other. One week after the HRMs tidying of the unit by the pharmacist, monthly audits were started and were carried out once a month, on Wednesdays, from June 2018 to October 2018. In addition, awareness information was posted every 2 months on the medicine cabinet of the unit. Compliance results were analysed using χ 2 and t tests for, respectively, all HRMs and HRMs classes. Results: The compliance for all 44 HRMs stored in the unit (64%–73%) was not significantly different between the different audits (p>0.05). No statistically significant differences (p>0.05) between the five audits were observed for insulin (43%–50% compliant), narcotics (100% compliant) and infusions (0% compliant): for the HRMs stored in the marked zone (67%–89% compliant), the difference between the months was not significant either, except between July (89% compliant) and August (67% compliant), where a significant decrease in compliance was observed (p<0, 05). This decrease was associated with a lack of awareness action between these 2 months. Conclusion: This work highlighted the improperly stored HRMs and showed that more awareness-raising actions need to be carried out to improve their tidying in a care unit. References and/or acknowledgements: Eur J Clin Pharmacol 2014;70:637–45. No conflict of interest.